2020
DOI: 10.1007/s00167-020-06208-w
|View full text |Cite
|
Sign up to set email alerts
|

The signal intensity of preoperative magnetic resonance imaging has predictive value for determining the arthroscopic reparability of the anterior talofibular ligament

Abstract: PurposeArthroscopic all‐inside anterior talofibular ligament (ATFL) repair is a common surgical technique for chronic ankle instability (CAI), and the condition of the ATFL remnants is associated with its reparability. ATFL reparability can affect the clinical course, but the relationship between magnetic resonance imaging (MRI) findings and the intraoperative ATFL reparability is still unclear. The purpose of this study was to investigate the relationship between ATFL signal intensities according to MRI and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…For each case, two slices were typically chosen for SNR measurements, which were then averaged to determine the final SNR value. The diagnostic SNR cutoff point for distinguishing between normal and abnormal but reparable ATFL was 11.2, and it took 32.3 to distinguish between an irreparable and reparable ATFL (Ahn et al, 2021).…”
Section: Mri Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…For each case, two slices were typically chosen for SNR measurements, which were then averaged to determine the final SNR value. The diagnostic SNR cutoff point for distinguishing between normal and abnormal but reparable ATFL was 11.2, and it took 32.3 to distinguish between an irreparable and reparable ATFL (Ahn et al, 2021).…”
Section: Mri Assessmentmentioning
confidence: 99%
“…The results revealed that the good ATFL condition group had a higher rate of return to sports than the poor ATFL condition group did, who had higher SNR values. According to ATFL tension and quality, Ahn et al also demonstrated that a low SNR evaluated by preoperative MRI predicted better ATFL reparability and that the SNR had predictive value to assess the ATFL reparability utilizing the arthroscopic all-inside ATFL repair procedure (Ahn et al, 2021). They confirmed that the diagnostic SNR cutoff point for differentiating between an aberrant but repairable ATFL and a normal ATFL was 11.2, and that it was 32.3 for differentiating between an irreparable ATFL and a repairable ATFL.…”
Section: Follow-up (Weeks) Control One Two P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…9). Ahn et al56 reviewed the signal intensity of the ATFL in 55 patients with ankle instability and correlated findings to the degree of tension found during arthroscopy and discovered that the lower signal intensity of the ligament predicted better ATFL repairability with respect to tension and quality. Animal models have shown that the signal intensity of a ligament correlates to the vascularity and tensile strength 57,58.…”
Section: Mrimentioning
confidence: 99%
“…Moreover, low accuracy is also observed in many studies [ 12 , 13 , 14 ] which could be due to the fact that it is a static exam used to study a structure that performs dynamic joint control. Further, it can potentially produce false negatives for ligament lesions, which would occur if the ligament was subjected to a yo-yo effect [ 11 , 13 , 15 , 16 , 17 , 18 ]. While staying at rest, it would exhibit a normal morphological structure, but leads to increased fiber elasticity, caused by a bad local collagen quality or quantity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%